CONSUMERS [WOMEN] PROTECTION AGAINST HAZARDOUS CHEMICALS IN PANTYLINER PRODUCTS - Puspa Wicha Ratnawicesa; Gianto Al Imron (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This study examines about the legal protection for the consumers of sanitary pad and pantyliner products which use the hazardous chemicals. The aim of this study is to reveal the responibility of government as the the supervisor of the sanitary pad and pantyliner products circulation, as well as to know the liability of the businessmen for the disadvantage suffered by the consumers of sanitary pad and pantyliner products.The researcher uses normative juridical method. As the results of this study are the responsibility of the government as the party who provides the standardization is contained in Legislation No. 102 of 2000 regarding national standardization; and as the consumer legal resistance to the businessmen is based on Article 19 of Act No. 8 of 1999 regarding consumer protection.The result of this study shows that the Government, as the the organizer of the distribution permission for sanitary pad and pantyliner, must strive to develop the legal products to create a product that is safe to be used by the society.